2013
DOI: 10.1111/mmi.12475
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the genetic basis of Moraxella catarrhalis complement resistance: a critical role for the disulphide bond formation system

Abstract: SummaryThe complement system is an important innate defence mechanism, and the ability to resist complement-mediated killing is considered a key virulence trait of the respiratory tract pathogen M. catarrhalis. We studied the molecular basis of complement resistance by transcriptional profiling and Tn-seq, a genome-wide negative-selection screenings technology. Exposure of M. catarrhalis to human serum resulted in increased expression of 84 genes and reduced expression of 134 genes, among which genes encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Furthermore, we detected a putative multidrug resistance (MDR) protein E (TcCLB.508965.14) highly upregulated in rdEpi ( p = 0.06); overexpression of a MDR P‐glycoprotein in a myeloid leukemia cell line confers resistance to complement‐mediated cytotoxicity (Weisburg et al ., ). Besides, recent studies showed that the disulfide bond formation system (Dsb) is critical for complement resistance in pathogenic bacteria (de Vries et al ., ; Ren et al ., ), suggesting that the development of Dsb inhibitors could have broad implications (Ren et al ., ). These may explain the up‐regulation of the T. cruzi ERO1 (eukaryotic endoplasmic reticulum oxidoreductin) only in rdEpi (Cluster 1), considered the eukaryotic equivalent of the Dsb system.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we detected a putative multidrug resistance (MDR) protein E (TcCLB.508965.14) highly upregulated in rdEpi ( p = 0.06); overexpression of a MDR P‐glycoprotein in a myeloid leukemia cell line confers resistance to complement‐mediated cytotoxicity (Weisburg et al ., ). Besides, recent studies showed that the disulfide bond formation system (Dsb) is critical for complement resistance in pathogenic bacteria (de Vries et al ., ; Ren et al ., ), suggesting that the development of Dsb inhibitors could have broad implications (Ren et al ., ). These may explain the up‐regulation of the T. cruzi ERO1 (eukaryotic endoplasmic reticulum oxidoreductin) only in rdEpi (Cluster 1), considered the eukaryotic equivalent of the Dsb system.…”
Section: Discussionmentioning
confidence: 99%
“…coli (YchF) belongs to the GTPase family and is a negative regulator of the oxidative stress response 53 . YchF proteins have been implicated in pathogenesis of other bacterial species 53, 54 . With branched-chain amino acids (BCAA) being linked to chemotaxis 55 , livM , part of the ABC-type BCAA transport system ( livM , livH , livK , and livJ ), may be implicated in within host chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular phylogenetic-typing methods, including restriction fragment length polymorphism analyses and multilocus sequence typing (MLST), have suggested that the M. catarrhalis species is composed of two main lineages ( Bootsma et al 2000a ; Pingault et al 2007 ; Wirth et al 2007 ), but that divergent strains with limited homology also exist ( Wirth et al 2007 ). The first described phylogenetic lineage, often referred to as the seroresistant (SR) lineage, contains 16S ribotype (RB) 1 strains and displays a more pathogenic profile as the vast majority of its members are complement resistant and adhere efficiently to respiratory epithelial cells ( de Vries et al 2013 , 2014 ). The other lineage, also known as the serosensitive (SS) lineage, consists of strains with RB2 and RB3, and mainly harbors M. catarrhalis isolates that are sensitive to complement-mediated killing and show less efficient adherence to respiratory epithelial cells ( Bootsma et al 2000a ; Pingault et al 2007 ; Wirth et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%